DIAGNOSIS AND MANAGENEBT OF TRANSPOSITION OF THE GREAT ARTERIES: FIRST FOUR CASES REPORTS AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate initially first four cases of d-transposition of the great arteries (d-TGA)were diagnosed and treated at Nghe An Obstetrics and Pediatrics HospitalMethods: To present four cases were first diagnosed and operated successfully with ASO. Thedata was taken from electronic medical records on EHC software of Nghe An Obstetrics andPediatrics Hospital. The information includes epidemiology, clinical symptoms, and subclinicalsymptoms before, during and after surgery.Results: Four patients were referred to Nghe An Obstetrics and Pediatrics Hospital at 14 days,2 month, 26 days, 1 day of age, no prenatal diagnosis, were diagnosed d-TGA after admission.Four patients underwent ASO successfully.Conclusions: There are still many difficulties to diagnose the d-TGA in prenatal and grassrootshealth care level. Nghe An Obstetrics and Pediatrics Hospital is a center that has ability todiagnose and perform ASO.
Keywords: Congenital heart defects, transposition of the great arteries, arterial switch operation.